Curriculum Design for TEFL/EFL in Indonesia: Navigating the Merdeka Curriculum Reform and National Education Standards: A Literature-Based Study - Fadhila Alya Fithri; Nurhalimah Nurhalimah; Febprianty Rusli; Kalayo Hasibuan (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
Lately, education in Indonesia has been getting a big shake-up from the Merdeka Curriculum reform, which really pushes for more flexibility, teaching that focuses on students, and assessments based on what they can actually do. This change hits hard for TEFL/EFL curriculum planning, needing to match up with national standards while dealing with what's really happening in classrooms. But from what the research shows, there's this ongoing struggle: lots of teachers and schools get the idea of the reform, yet putting it into action often falls short. For instance, studies point out that even though most schools say they understand the Merdeka Curriculum clearly, things like not enough teacher training and limited resources get in the way of real progress (Sephiawardani & Bektiningsih, 2023; Andika & Yulia, 2025). Other work highlights how English teachers, despite being eager, have trouble tweaking assessments, planning lessons that suit different kids, and creating materials that fit the local scene (Karimatunisa & Sartika, 2024; Andika & Yulia, 2025). This review of the literature aims to chart out how recent studies (2021–2025) describe TEFL/EFL curriculum design amid these changes, spot the big gaps, and suggest ways forward for better curriculum development. From what we've pulled together, things like teacher training, ongoing help, and better ways to turn policies into classroom reality are key to closing the gap between the reform's goals and what's actually happening in schools.